Study of B+c meson decays to charmonia plus multihadron final states - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Caspary, Rowina; Frau, Giulia; Gerick, David; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; et al. (Journal of high energy physics, 2023)
Four decay modes of the $$ B_c^{+} $$meson into a J/ψ meson and multiple charged kaons or pions are studied using proton-proton collision data, collected with the LHCb detector at centre-of-mass energies of 7, 8, and 13 TeV and corresponding to an integrated luminosity of 9 fb−1. The decay $$ B_c^{+} $$ → J/ψK+K−π+π+π− is observed for the first time, and evidence for the $$ B_c^{+} $$ → J/ψ4π+3π− decay is found. The decay $$ B_c^{+} $$ → J/ψ3π+2π− is observed and the previous observation of the $$ B_c^{+} $$ → ψ(2S)π+π+π− decay is confirmed using the ψ(2S) → J/ψπ+π− decay mode. Ratios of the branching fractions of these four $$ B_c^{+} $$decay channels are measured.
*The LHCb collaboration: R. Aaij, F. Archilli, S. Bachmann, D. Berninghoff, M. Borsato, R. Caspary, G. Frau, D. Gerick, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, R. Kopecna, B. Leverington, P. Li, J. Marks, D.J. Unverzagt, U. Uwer, C. Witola, A. Zhelezov (und sehr viele weitere Personen)
Im Titel ist Pluszeichen hoch- und der Buchstabe "c" tiefgestellt
Gesehen am 22.05.2024